Adult triploid Atlantic salmon (Salmo salar) have higher dietary histidine requirements to prevent cataract development in seawater. (7th April 2014) - Taylor, J.F.; Waagbø, R.; Diez‐Padrisa, M.; Campbell, P.; Walton, J.; Hunter, D.; Matthew, C.; Migaud, H.
Abstract The study investigated cataract preventive effects of dietary histidine (His) supplementation in triploid Atlantic salmon during seawater grow‐out. Groups of individually PIT tagged diploid (2N) and triploid (3N) postsmolts were fed one of two supplemented dietary histidine levels; low (L, 12.6 g kg−1 diet) or high (H, 17.4 g kg−1 diet) from March to September following their first sea winter. Low severity cataracts were detected in both ploidy prior to supplemented His diet application. Thereafter, 3N‐L showed progression of cataract development in the second spring‐summer period, while development was inhibited in 3N‐H. Severity of cataract showed a strong family effect. A positive correlation between initial triploid seawater growth (weight and TGC) under increasing water temperature and cataract severity was identified as a major risk factor. The relationship was reversed at harvest, where triploids were on average 7.5% smaller than their diploid siblings. Lens N‐acetyl‐histidine content reflected dietary His inclusion level and cataract severity, although no significant differences in lens His content were evident between ploidy or dietary groups. Results indicate that triploid Atlantic salmon appear to have a higher dietary histidine requirement than diploids and that preventative measures can be taken to mitigate further cataract development.